Discovery of the spider wasp genus Sphictostethus Kohl, 1884 (Hymenoptera: Pompilidae: Pepsinae) in New Guinea, with description of two new species - Loktionov, Valery M.; Lelej, Arkady S. (Zootaxa, 2018)
Two new species of the genus Sphictostethus Kohl, 1884 are described and illustrated from New Guinea (Indonesia: West Papua). Both species, S. papua Loktionov & Lelej, sp. nov. and S. arfak Loktionov & Lelej, sp. nov. differ from congeners by their peculiar head and clypeus shape, the presence of tubercles on the mesopleuron and propodeum, and the well-developed metasomal petiole. The genus Sphictostethus is newly recorded from New Guinea as a new northernmost border for their distribution within the Australian Region. An addition to the key of Australian species is given.